Retraction Note: MDMA-assisted psychotherapy for treatment of PTSD: study design and rationale for phase 3 trials based on pooled analysis of six phase 2 randomized controlled trials - Michael C. Mithoefer; Allison A. Feduccia; Lisa Jerome; Anne Mithoefer; Mark Wagner; Zach Walsh; Scott Hamilton; Berra Yazar-Klosinski; Amy Emerson; Rick Doblin (Psychopharmacology, 2024)

RETRACTED ARTICLE: MDMA-assisted psychotherapy for treatment of PTSD: study design and rationale for phase 3 trials based on pooled analysis of six phase 2 randomized controlled trials - Michael C. Mithoefer; Allison A. Feduccia; Lisa Jerome; Anne Mithoefer; Mark Wagner; Zach Walsh; Scott Hamilton; Berra Yazar-Klosinski; Amy Emerson; Rick Doblin (Psychopharmacology, 2019)
Background Posttraumatic stress disorder is a prevalent mental health condition with substantial impact on daily functioning that lacks sufficient treatment options. Here we evaluate six phase 2 trials in a pooled analysis to determine the study design for phase 3 trials of MDMA-assisted psychotherapy for PTSD. Methods Six randomized, double-blind, controlled clinical trials at five study sites were conducted from April 2004 to February 2017. Active doses of MDMA (75–125 mg, n = 72) or placebo/control doses (0–40 mg, n = 31) were administered to individuals with PTSD during manualized psychotherapy sessions in two or three 8-h sessions spaced a month apart. Three non-drug 90-min therapy sessions preceded the first MDMA exposure, and three to four followed each experimental session. Results After two blinded experimental sessions, the active group had significantly greater reductions in CAPS-IV total scores from baseline than the control group [MMRM estimated mean difference (SE) between groups − 22.0 (5.17), P < 0.001]. The between-group Cohen’s d effect size was 0.8, indicating a large treatment effect. After two experimental sessions, more participants in the active group (54.2%) did not meet CAPS-IV PTSD diagnostic criteria than the control group (22.6%). Depression symptom improvement on the BDI-II was greatest for the active group compared to the control group, although only trended towards significant group differences [MMRM, estimated mean difference (SE) between groups − 6.0 (3.03), P = 0.053]. All doses of MDMA were well tolerated, with some expected reactions occurring at greater frequency for the active MDMA group during experimental sessions and the 7 days following. Conclusions MDMA-assisted psychotherapy was efficacious and well tolerated in a large sample of adults with PTSD. These studies supported expansion into phase 3 trials and led to FDA granting Breakthrough Therapy designation for this promising treatment. Trial registration ClinicalTrials.gov Identifier: NCT00090064, NCT00353938, NCT01958593, NCT01211405, NCT01689740, NCT01793610.